Applicability of enhancement factor models for CO2 absorption into aqueous MEA solutions. (15th November 2017) - Putta, Koteswara Rao; Tobiesen, Finn Andrew; Svendsen, Hallvard F.; Knuutila, Hanna K.
Highlights: Enhancement factor models were tested for CO2 absorption using aqueous MEA solution. 24 models were tested against experimental data from four lab scale set-ups. Enhancement factor models accuracy and validity were analyzed quantitatively. Out of 24 only few models predict the experimental CO2 fluxes satisfactorily. Few models were found to work equally well as the discretized penetration model. Abstract: In many chemical industrial processes, mass transfer across gas-liquid interfaces accompanied by chemical reaction is the governing phenomena. In case of mass transfer accompanied by a chemical reaction in the liquid phase, the reaction will enhance mass transfer and generally the mass transfer enhancement is quantified in terms of an enhancement factor. Large number of enhancement factor models have been developed in literature and used without critical analysis for analyzing pilot data for CO2 absorption into aqueous amines. In order to perform such a critical analysis, 24 models are tested using lab-scale experimental data from four independent apparatuses for CO2 absorption into MEA solutions covering a range of different conditions such as short and long contact times, with and without gas phase resistance, high and low CO2 loadings and temperatures. Of the 24 enhancement factor models tested only six models were found to satisfactorily predict the experimental CO2 fluxes. These were the models based on the simple pseudo-first order reaction assumption, Emodels 1, 2 and 3 by Hatta [2] and Dankwerts [4] respectively, Emodel 20, the deCoursey and Thring [44] model based on Danckwert's surface renewal theory with unequal diffusivities, Emodel 24, the recently published generalized model by Gaspar and Fosbøl [51] and Emodel 21, the Tufano et al. [67] model based surface renewal theory. All these models were found to work equally well to the discretized penetration model. No significant difference was found between Emodels 1, 2 and 3, indicating that whether one uses as basis a film, penetration or surface renewal model, is of insignificant importance. The success of the simple models is attributed to the short contact times in the experiments used as basis and the accuracy of the kinetic model. Contact times of the same magnitude between mixing points is also encountered in industrial packings and it is believed that the simple enhancement factor models may work well also in these cases if an accurate kinetic model is used.